MATHEMATICAL MODELING OF VARIANTS OF TRANSPEDICULAR FIXATION AT THE THORACOLUMBAR JUNCTION AFTER ТHХІІ VERTEBRECTOMY DURING TRUNK BACKWARD BENDING - Nekhlopochyn, Oleksii; Verbov, Vadim; Cheshuk, Ievgen; Karpinsky, Mykhailo; Yaresko, Olexander (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Fractures at the thoracolumbar junction are the most common traumatic spinal injuries. Advances in instrumentation for vertebral body replacement have significantly improved surgical techniques. However, the biomechanical characteristics of stabilizing surgeries have been insufficiently studied. Objective. To investigate the stressstrain state (SSS) of a mathematical finite element model of the human thoracolumbar spine during trunk backward bending after ТhХІІ vertebra resection, considering different transpedicular fixation options. Methods. A mathematical finite element model of the human thoracolumbar spine — ThIX‒LV vertebrae — was developed. The ТhХІІ vertebra was removed, and an interbody support and transpedicular system with 8 screws were implanted to simulate the postsurgical state after a ТhХІІ burst fracture with wide laminectomy, facetectomy, and corpectomy. The influence of transpedicular screw length and the presence of cross-links on the SSS of the model was examined. Results. The use of bicortical screws reduced stress levels in the bone elements of the model, except in the regions around the screws in the lumbar vertebrae, when compared to short screws. Installing cross-links decreased stress levels at all control points compared to models without cross-links. Specifically, in the presence of cross-links, the SSS values at the entry points of the short screws into the vertebral bodies of ThX, ThXI, LI, and LII were 2.3, 1.8, 1.2, and 5.0MPa, respectively, compared to 2.7, 2.0, 1.5, and 6.1 MPa in the models without cross-links. In the case of bicortical screws without cross-links, the stress values at the screw entry points into the pedicles of the corresponding vertebrae were 2.9, 1.5, 8.2, and 11.2 MPa, respectively, compared to 2.7, 1.5, 7.5, and 10.2 MPa in the models with cross-links. Conclusions. When the trunk is tilted backward, the use of cross-links reduces stress levels at all control points in the models, regardless of the screw length used. Bicortical transpedicular screws increase stress levels on the screws themselves and in the lumbar vertebral bodies surrounding them.